Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Environmental Contamination and Childbirth. Issue 4 (October 2020) - Hermesch, Amy C.; Horve, Patrick F.; Edelman, Alison; Dietz, Leslie; Constant, David; Fretz, Mark; Messer, William B.; Martindale, Robert; Van Den Wymelenberg, Kevin
Abstract : Patients with asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection give rise to SARS-CoV-2 environmental contamination during childbirth.